So you want to solve
log [base 1/6] (6x^2).
And you want to solve it using only natural logarithms, or log[base e], or ln.
The first thing to note is that, using the log property
log[base b](ac) = log[base b](a) + log[base b](c)
we can change the form of that log to
log[base 1/6](6) + log[base 1/6](x^2)
Also, using the log property that
log [base b](a^c) = c * log[base b](a),
log[base 1/6](6) + 2 log[base 1/6](x)
One thing to note is that if we let y = log[base 1/6](6), we can actually reduce the log itself.
y = log[base 1/6](6). Changing this into exponential form, we get
(1/6)^y = 6, or
( [6]^(-1) )^y = 6, or
6^(-y) = 6^1
So we can equate the exponents to get
-y = 1, or
y = -1.
So log[base 1/6](6) = -1. Substituting this in, we get
-1 + 2 log[base 1/6](x)
Now, we use the change of base formula to convert our current logs into natural logs, ln. Note that the change of base formula goes as follows:
log[base c](a) = log[base b](a) / log[base b](c), where we can choose b to be *any* base.
In this case we want b to be e, so we'll end up with ln.
-1 + 2 log[base 1/6](x)
-1 + 2 {ln (x)} / {ln(1/6)}
Note that ln(1/6) = ln(6^(-1)) = -ln(6), so we can have
-1 + 2 [ln(x)] / [-ln(6)], or
-1 - 2 ln(x)/ln(6)
2006-12-24 07:23:17
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
Now that's a weird base. 1/6. As an enumeration base, it's a little unusual. For example, thirty-six is 0.01 in that base. Now if it were 1/7, since 7 is prime, you would get a really interesting notation, completely redefining distance, by using powers of 7; something called 7-adic numbers.
But that's another topic. To solve this, use the identity:
log(a)b = log(x)b/log(x)a,
where a, b, and x are any numbers that can be used as bases for logarithms (i.e., don't use 0, 1, or negative numbers).
In your case,
log(1/6)6x^2 = log(1/6)6 + 2 log(1/6)x
= log(6)(6)/log(6)(1/6) + 2 log(e)(x)/log(e)(1/6)
= 1/(-1) + 2 ln(x)(-ln 6) = -(2/ln6) ln(x) - 1
2006-12-24 09:01:27
·
answer #2
·
answered by alnitaka 4
·
0⤊
0⤋
for the logarithm of a nunber in other bases, we have the formula
log_a_(b) = log(b)/log(a) = ln(b)/ln(a)
where a is the base and b is the argument of the logarithm
so if we used this in your expression
log_(1/6)_6*x^2 with a = 1/6 and b = 6*x^2
log_(1/6)_6*x^2 = ln(6*x^2)/ln(1/6) = 2*ln(6*x)/ln(1/6)
2006-12-24 08:15:36
·
answer #3
·
answered by ProzeB 2
·
0⤊
0⤋
Could you rephrase your question or something. Natural logarithms are base e. You say the base of this problem is (1/6).
2006-12-24 07:23:47
·
answer #4
·
answered by edgar 1
·
0⤊
0⤋
By the change of base formula log_b_(x) = ln(x)/ln(b)
So it's ln(6x^2) / ln(1/6)
2006-12-24 07:29:11
·
answer #5
·
answered by Professor Maddie 4
·
0⤊
0⤋
log_(1/6)_6x^2=ln 6x^2 *ln 1/6
ln 6x^2 *ln 1/6
2006-12-24 08:42:31
·
answer #6
·
answered by mu_do_in 3
·
0⤊
0⤋
ln(6x^2)/ln(1/6)
=(ln6 + 2lnx)/(-ln6)
=-1 - 2 lnx/ln6
2006-12-24 07:13:54
·
answer #7
·
answered by sahsjing 7
·
0⤊
0⤋